Analysis That Influences The Quality of Nursing Services in Installations of Colonel Abunjani Hospital, Bangko in 2019 - Juang Abdi Eliezer Dakhi; Sri Lestari Ramadhani Nasution; Ermi Girsang; Tan Suryono (International Journal of Health and Pharmaceutical (IJHP), 2022)
The implementation of hospital health services in Indonesia currently faces increasingly complex challenges. The improvement of hospital quality must be improved in accordance with the development of the needs and demands of the community, accompanied by an increase in efficiency and productivity in the field of management, in accordance with the hospital's minimum service standards, professional standards, and standard operating procedures. The study aims to determine the relationship of knowledge, skills, behavior, education, experience, and motivation of nurses with the quality of nursing services at the kolonel abunjani bangko Hospital in 2019. This observational analytic study uses a Cross Sectional design. Chi square statistical test and multiple logistic regression regression were used to analyze data. The population and sample size in this study were 92 nurses where data collection was taken from the results of the questionnaire. The results of the bivariate analysis showed that there was a relationship of knowledge, skills, behavior, potential, education, experience, and motivation with the quality of nursing services at the kolonel abunjani bangko Hospital in 2019. The results of multivariate analysis showed that experience was the most dominant variable affecting quality service. Conclusions obtained are the relationship of knowledge, skills, behavior, potential, education, experience, and motivation of nurses with the quality of nursing services in kolonel abunjani bangko Hospital in 2019. It is recommended to the hospital, to continue to improve knowledge, skills, behavior, education, experience, and continuous motivation. By increasing competence and continuous performance, the nurse's weaknesses and strengths can be known. Thus, good nurse competency can give satisfaction to patients and provide job promotion so as to improve the work performance of nurses so that they can increase the quality of health services.